The Effectiveness of Writing Warm-Ups Strategy to Students’ Writing Skill - Ramasari, Maria (ELT-Lectura, 2021)
Writers need to have a warming up before beginning to write. It is the fundamental thing to be done by students as writers for stimulating their critical thinking. It is also useful for them to be easier in developing their ideas at writing activities. The objective of this research investigation was to find out an effectiveness of writing warm-ups strategy on students’ writing skill: report text. Research method used was pre-experimental with only one group pre-test and post-test design. Population was all the seventh grade students of SMP Negeri H. Wukirsari which consisted of 139 students. Sample was taken through cluster random sampling, and number of sample was only 28 students. Written test (report text) was given to students’ sample in collecting the data. In analyzing the data, researcher used individual score, Mastery Minimum Criteria, and matched t-test. Based on the data analysis, the students’ mean score of pre-test was 54.67 and students’ mean score of post-test was 75.10. Result of t-test was 3.88 and t-table was 1.701 since the degree of freedom significant level of it one tailed test. Hence, matched t-test was higher than t-table. For other words, it meant that alternative hypothesis was accepted, and null hypothesis was rejected. In conclusion, it was completely effective to apply writing warm-ups strategy on students’ writing skill of report text.